Geology and Properties of Materials Exposed in the USACRREL Permafrost Tunnel. - Sellmann,Paul V. (1972)
The U.S. Army Cold Regions Research and Engineering Laboratory (USA CRREL) permafrost tunnel near Fiarbanks, Alaska, was recently enlarged. A new winze and lower room were constructed in the tunnel, permitting examination of new silt exposures and previously unexposed, stratigraphically lower gravels and bedrock. From these exposures additional stratigraphic information was obtained by radiocarbon dating; new data on the material properties of the perennially frozen gravels were also acquired. (Author)